On the influence of acidic admixtures in furfural on the performance of MgAl mixed oxide catalysts in aldol condensation of furfural and acetone - Kikhtyanin, O; Korolova, V; Spencer, A; Dubnová, Lada; Shumeiko, B; Kubicka, D (Elsevier Science BV, 2021)
Aldol condensation of furfural and acetone is often used as a model reaction to test acid-base properties of solid catalysts. The present study describes the effect of furfural acidity on the catalytic performance of MgAl mixed oxides. Three furfural sources differing in their acidity were used and compared in aldol condensation at T = 55 ?C and acetone to furfural molar ratio of 10. The furfural conversion over MgAl mixed oxides depended on the acidity of the furfural source, and the catalysts were partially consumed for neutralization of acid admixtures present in furfural. Only for some furfurals could the furfural conversion be improved by distilling the as-received furfural prior to the aldol condensation experiments. Moreover, the storage of the freshly distilled furfural during a few days, even in a closed flask and at a dark place, resulted in a substantial decrease in furfural conversion in aldol condensation. The results indicate that the distillation of the as-received furfural is an effective method to control the performance of basic catalysts at comparable reaction conditions only for some furfurals. Furthermore, the storage of the freshly distilled furfural has to be performed with care to avoid its re-oxidation.
Vliv kyselých přísad ve furfuralu na účinek MgAl směsných oxidových katalyzátorů v aldolové kondenzaci furfuralu a acetonu
Keywords: aldol condensation; furfural; acetone; basic catalysts; mixed oxides; acid impurities; aldolová kondenzace; furfural; aceton; katalyzátory; směsné oxidy; kyselé nečistoty